Impact of Celebrity Endorsements on Consumers’ Ad Perception: A Study Of Indian Consumers - Gupta, Ruchi; Kishore, Nawal; Verma, DPS (British Journal of Marketing Studies, 2015)
Numerous researches have proved empirically the effectiveness and the positive influence of celebrity endorsements in advertising. The present study attempts to find out the impact of celebrity endorsements on consumers’ ad perception through a survey of 336 respondents in India. The three-dimensional scale proposed by Roobina Ohanian (1990) has been used for the purpose. Thus, the present study considers three attributes of celebrity endorsements as suggested by Ohanian - attractiveness, trustworthiness and expertise. The study also attempts to find out the individual impact of these dimensions on consumers’ ad perception. Exploratory factor analysis was used to reconfirm the factor structure. The model used was empirically tested for unidimensionality, reliability, convergent validity and discriminant validity, using confirmatory factor analysis. Structural equation modeling was used to find out the impact of celebrity endorsements on consumers’ ad perception. Results revealed that celebrity endorsements have a significant impact on consumers’ ad perception. Further, attractiveness, trustworthiness and expertise, all were found to have a significant impact on ad perception.